Determinants of Micro-Insurance Ownership Decision: Empirical Evidence from Informal Commercial Market Business Operators in Ghana - Yeboah, Augustine Kwadwo (Journal of Social and Development Sciences, 2018)
This study empirically examines determinants of Micro-insurance ownership decision in Ghana. Probit estimation technique was used to examine data sourced from 612 informal commercial business operators in selected urban market centers in Ghana. The results reveal that financial literacy has significant effect on micro-insurance ownership decision among informal commercial market business operators in Ghana. The study also found income, access to credit, trust, market levy, Marital status and household headship status as other major predictors of micro-insurance ownership decision. Premised on these, the study recommends financial literacy education intervention by micro-insurance providers to increase microinsurance patronage. Micro-insurance providers should invest in building reputation to encourage participation in micro-insurance scheme. Also, efforts of government should focus on improving access to credit facilities and income generation prospects among informal businesses operators in Ghana.